The Effect of Land Use and Traffic Performance on Urban Air Quality in the Maminasata Peri-Urban Area - Sri Hidayat; Andi Agustang; Nurlita Pertiwi (Budapest International Research and Critics University, 2022)
The corridor of the Hertasning-Tun Abdul Razak road section is a peri-urban area that is experiencing high dynamics due to the need for housing and new facilities for activities. This manifests a spatial transformation. Spatial transformation has an impact on increasing anthropogenic activity which can reduce air quality. Increased journal anthropogenic activity with land use and performance across corridors. This research uses quantitative methods to measure the relationship between variables using land, traffic performance, and climatic conditions to air quality with data analysis using SEM PLS. The results of the hypothesis statistically on the effect of each independent variable on the dependent variable on land use have a significant effect on climatic conditions and air quality. However, land use variables have a dominant influence on air quality. Meanwhile, the analysis of the indirect effect shows that there is no indirect effect between land use and traffic performance on air quality. This shows that climatic conditions are not a mediating variable. The results of the analysis also show that there are only 2 valid land use indicators showing the effect, namely the use of grass land and water bodies. This explains that the increased built-up area on the Hertasning-Tun Abdul Razak road corridor does not affect air quality, but what affects air quality is the dominance of anthropogenic activities that can release emissions into the air. Anthropogenic activities that affect air quality are expected to come from open dumping, smoke pollution from fish combustion systems, and emissions from domestic waste that enter air bodies.